Latin America Region: Between Dependence and Autonomy in Regional Processes - Wendy Vaca Hernández (Íconos)
The space called Latin America has a particular history marked by centuries of colonialism and coloniality. The latter concept implies that the basic structure of the colonial system has not changed even though formal independence has been achieved. For this reason, the subcontinent has fluctuated between dependence and the quest for autonomy. These successive cycles have manifested themselves both in the internal configurations and in the regional schemes that have been undertaken. This paper analyzes the construction and evolution of the idea of a region: Latin America and the Caribbean. To that end it examines the concepts of region, regionalism, what Latin America and the Caribbean implies, and what are the transformations in these ideas that have emerged from the regional configurations of the Union of South American Nations (UNASUR) and the Community of Latin American and Caribbean States (CELAC) as plural organisms with broad objectives.